Effect of Concept Mapping on Developing Clinical Judgement Among 2nd Year BSc Nursing Students - Sikha, Kapil Adarsh; Devi, Samuel (JOURNAL OF CLINICAL AND BIOMEDICAL SCIENCES, 2025)
Background: Nursing program aims to provide students with the necessary skills to apply sound clinical judgment. Concept mapping fosters meaningful learning and promotes critical thinking abilities that are essential for achieving this goal. Objective: To evaluate the effectiveness of concept mapping methods among nursing students in developing clinical judgement skills. Materials and Methods: A quasi-experimental pretest-post-test study design was adopted. The study was conducted at Krupanidhi College of Nursing, affiliated with Rajiv Gandhi University of Health Sciences (RGUHS). A convenient sample of 41 second-year undergraduate nursing students during the academic year 2022-2023 were divided randomly into experimental groups (n=103) and control groups (n=103). The students were given case scenarios and asked to make a care plan, and their clinical judgement was evaluated. After a few days of the pre-test, the same group of students were given the same case scenarios and asked to make a concept mapping to prepare a care plan. Then, the clinical judgement of the students was evaluated. Pearson Chi-square and Paired t-test were used for statistical analysis. Result: Most of the students (n=4; 9.75%) were in the age group 20 years, and females were predominant (n=30; 73.2%) compared to males (n=11;26.8%). Most subjects, 34.1%, were Hindu, followed by 31.7% Christians, 24.4% Buddhist and 9.8% Muslim. The results showed a statistically significant difference between pre- and post-awareness sessions among the study group regarding concept mapping on clinical judgement (p<0.05). There was no correlation between the students' pre- and post-test clinical judgement skills with demographic variables (p>0.05), except for the pre-test clinical judgement skills with gender. Conclusion: Using concept mapping may provide an interactive way to foster the growth of clinical judgment skills in nursing students. Keywords: Concept mapping, Clinical judgement, Mind mapping, Clinical reasoning, Problem solving